Risk Factors for PoorAutologous Peripheral blood Stem Cell Mobilization among Lymphoproliferative Disease Patients (Bangladesh Journal of Medical Science, 2020)
Objective: Autologous peripheral blood haemopoietic stem cell (PBSC) transplantation is a standard therapeutic option for eligible patients with lymphoproliferative disease (LPD). The prerequisite for autologous PBSC transplantation is the successful stem cell mobilization. This study is aimed to determine the factors associated with poor PBSC mobilization in LPD patient at our center.Materials and methods: This retrospective record review involved 39 multiple myeloma (MM) and 92 of lymphoma patients who had undergone PBSC mobilization from January 2009 until December 2016. Patients were mobilized with combination chemotherapy and granulocyte colony stimulating factor. Factors affecting mobilization including patient’s, disease and treatment characteristics werestudied.Results: Majority of patients were Malay (93.9%) with the mean age at mobilization of 41.4 years. The mean of CD34+ cell dosage was 9.6x106 cells/kg. Successful and poor mobilization was found to be 90.8% and 9.2% respectively. Multivariate analysis showed that the significant risk factors for poor mobilization were age of ≥ 60 years (adjusted OR=38.43, p=0.005) and PB CD34+ cell count,